Stress-related psychosocial intervention among pregnant woman with history of miscarriage: A scoping review - Karisa, Putri; Rukmasari, Ema Arum; Al Fajar, Muhamad Gustaf (Pediomaternal Nursing Journal, 2024)
Introduction: Miscarriage is a traumatic experience for the mother and can lead to stress due to lack of family and social support. This event can be harmful to the woman as it can lead to pregnancy trauma and more severe psychological disorders such as depression and suicide. Providing psychosocial support to women experiencing miscarriage can be a positive supportive care option.  This article aimed to identify psychosocial interventions to reduce stress levels in pregnant women with a history of miscarriage. Method: A scoping review was conducted using PubMed, Google Scholar, Science Direct, and SAGE Journal databases. Keywords used include psychosocial intervention, stress level, and pregnancy. Articles were selected based on the criteria of publication year 2017-2022, English language, randomized controlled trial research design and research results according to the topic. Results: The results obtained 6 articles that met the criteria. Psychosocial interventions to reduce stress levels in pregnant women with a history of miscarriage can be done through mindfulness therapy, supportive care, family support, brief supportive psychotherapy, cognitive narrative intervention, and happiness counseling programs. Conclusions: Psychosocial-based interventions can be used as supportive therapy to improve the psychological well-being of women with a history of miscarriage. Keywords: miscarriage; pregnancy; psychosocial intervention; stress level